Solving multi-criteria scheduling flow shop problem through compromise programming and satisfaction functions - Allouche, Mohamed Anis; Aouni, Belaïd; Martel, Jean-Marc; Loukil, Taïcir; Rebaï, Abdelwaheb (European journal of operational research, 2009)
The multi-criteria scheduling problem is one of the main research subjects in the field of multiple objectives programming. Several procedures have been developed to deal with this type of problem where some conflicting criteria have to be optimized simultaneously. The aim of our paper is to propose an aggregation procedure that integrates three different criteria to find the best sequence in a flow shop production environment. The compromise programming model and the concept of satisfaction functions will be utilized to integrate explicitly the manager’s preferences according to the deviations between the achievement and the aspiration levels of the following criteria: Makespan, total flow time and total tardiness.